Discovery of the FDA-approved drugs bexarotene, cetilistat, diiodohydroxyquinoline, and abiraterone as potential COVID-19 treatments with a robust two-tier screening system. (September 2020) - Yuan, Shuofeng; Chan, Jasper F.W.; Chik, Kenn K.H.; Chan, Chris C.Y.; Tsang, Jessica O.L.; Liang, Ronghui; Cao, Jianli; Tang, Kaiming; Chen, Lin-Lei; Wen, Kun; Cai, Jian-Piao; Ye, Zi-Wei; et al.
Graphical abstract: Abstract: Coronavirus Disease 2019 (COVID-19) caused by the emerging severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is associated with a crude case fatality rate of about 0.5–10 % depending on locality. A few clinically approved drugs, such as remdesivir, chloroquine, hydroxychloroquine, nafamostat, camostat, and ivermectin, exhibited anti-SARS-CoV-2 activity in vitro and/or in a small number of patients. However, their clinical use may be limited by anti-SARS-CoV-2 50 % maximal effective concentrations (EC50 ) that exceeded their achievable peak serum concentrations (Cmax), side effects, and/or availability. To find more immediately available COVID-19 antivirals, we established a two-tier drug screening system that combines SARS-CoV-2 enzyme-linked immunosorbent assay and cell viability assay, and applied it to screen a library consisting 1528 FDA-approved drugs. Cetilistat (anti-pancreatic lipase), diiodohydroxyquinoline (anti-parasitic), abiraterone acetate (synthetic androstane steroid), and bexarotene (antineoplastic retinoid) exhibited potent in vitro anti-SARS-CoV-2 activity (EC50 1.13–2.01 μM). Bexarotene demonstrated the highest Cmax:EC50 ratio (1.69) which was higher than those of chloroquine, hydroxychloroquine, and ivermectin. These results demonstrated the efficacy of the two-tier screening system and identified potential COVID-19 treatments which can achieve effective levels if given by inhalation or systemically depending on their pharmacokinetics.